2021
DOI: 10.1099/acmi.0.000259
|View full text |Cite
|
Sign up to set email alerts
|

High SARS-CoV-2 viral load is associated with a worse clinical outcome of COVID-19 disease

Abstract: COVID-19 severity and progression are determined by several host and virological factors that may influence the final outcome of SARS-CoV-2-infected patients. The objective of this work was to determine a possible association between viral load, obtained from nasopharyngeal swabs, and the severity of the infection in a cohort of 448 SARS-CoV-2-infected patients from a hospital in Madrid during the first outbreak of the pandemic in Spain. To perform this, we clinically classified patients as mild, moderate and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…We previously classified 448 patients (Fundación Jiménez Díaz [FJD] cohort, Madrid, Spain, April 2020) according to the COVID-19 severity into three categories, mild, moderate, and severe COVID-19, based on a number of demographic and clinical parameters, and we found a positive association between viral load in nasopharyngeal swabs and disease severity ( 37 ). For the present study, we have chosen 30 of the nasopharyngeal samples based on three criteria: (i) the COVID-19 category, including 10 patients who developed mild symptoms, 10 patients who developed moderate disease, and 10 patients who progressed to severe disease and exitus, (ii) patients whose diagnostics (real-time PCR RNA samples) displayed similar cycle threshold [ C T ] values (average C T of 25.37 ± 3.9 for mild, C T of 21.81 ± 2.4 for moderate, and C T of 20.38 ± 2.9 for exitus patients), and (iii) similar time interval between symptom onset and swab collection (average 5.78 ± 4.2 days for mild, 4.89 ± 3.1 days for moderate, and 4.5 ± 2.6 days for exitus patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously classified 448 patients (Fundación Jiménez Díaz [FJD] cohort, Madrid, Spain, April 2020) according to the COVID-19 severity into three categories, mild, moderate, and severe COVID-19, based on a number of demographic and clinical parameters, and we found a positive association between viral load in nasopharyngeal swabs and disease severity ( 37 ). For the present study, we have chosen 30 of the nasopharyngeal samples based on three criteria: (i) the COVID-19 category, including 10 patients who developed mild symptoms, 10 patients who developed moderate disease, and 10 patients who progressed to severe disease and exitus, (ii) patients whose diagnostics (real-time PCR RNA samples) displayed similar cycle threshold [ C T ] values (average C T of 25.37 ± 3.9 for mild, C T of 21.81 ± 2.4 for moderate, and C T of 20.38 ± 2.9 for exitus patients), and (iii) similar time interval between symptom onset and swab collection (average 5.78 ± 4.2 days for mild, 4.89 ± 3.1 days for moderate, and 4.5 ± 2.6 days for exitus patients).…”
Section: Resultsmentioning
confidence: 99%
“…The cohort of the study included 30 patients admitted to the Fundación Jiménez Díaz Hospital (FJD, Madrid, Spain) from 3 to 29 April 2020. All patients were confirmed to be positive for SARS-CoV-2 by a specific real-time PCR (VIASURE) with a C T (cycle threshold, which is inversely correlated with viral RNA level) range of 15.6 to 28.5; the samples are a subset from the cohort that has been described previously in reference 37 . Data collected included patient demographics, risk factors for COVID-19, and clinical information at the time of SARS-CoV-2 diagnosis (Table S1 in https://saco.csic.es/index.php/s/8GH5aJgritCjEx5 ).…”
Section: Methodsmentioning
confidence: 99%
“…pDCs link innate and adaptive immunity and one of their key functions is the production of IFN-I in response to viral or bacterial infections [ 59 ]. Depletion of pDCs could therefore result in a reduced ability to detect and limit viraemia since high viral loads have been associated with severe disease [ 60 ]. Changes in the composition of adaptive immune cells are associated with disease progression and it is reported that severe and critical COVID-19 patients present dramatically decreased natural killer cells (NK cells) on admission to hospital [ 43 , 49 , 53 ].…”
Section: Association Of Alterations Of Cell Populations and Covid-19 ...mentioning
confidence: 99%
“…Many studies have suggested that the SARS-CoV-2 viral load might predict the potentiality of disease severity and transmission. In the 2020 SARS-CoV epidemic, a higher viral load was related to increase emergency care requirements, intensive care, and overall poor prognosis [30], [31]. [32].…”
Section: Discussionmentioning
confidence: 99%